The Barriers in the Implementation of Antimicrobial Stewardship Programs (Asian Journal of Pharmaceutics (AJP), 2021)
The resistance to antimicrobial is considered one of the most important risks that affect public health and healthcare. Antimicrobial stewardship programs (ASPs) contain a series of interventions that decrease the inappropriateuse of antimicrobials. There are many barriers to the implementation of ASPs. To improve the use of antibiotics,it is important to overcome these barriers. In the present study, we searched for articles about the barriers ofimplementing ASPs using the keyword â€œASPsâ€ in the PubMed database. The present study found that the mostcommon hurdles are lack of training, knowledge, interprofessional conflict, interspecialty conflict, and lack ofresources.